Girls; the latest. A study of female dropout in Central Kibosho (Tanzania) - John, Felista; Francisco, Andrea; Moliner, Lidón (Profesorado, Revista de Currículum y Formación del Profesorado, 2015)
One of the Millennium Development Goals for 2015 was to achieve universal access to primary education for everyone; but there are still 58 million children between 6 and 11years old out of school; a situation that affects mainly girls. The lowest rates of primary school enrolment are at subsaharan Africa; Where only 65% of children attend school (UNESCO; 2014). To this situation; we have to add that one of every three girls leave education and doesn´t access to secondary school (Plan; 2012). Given this background; this research aims to explore the factors that contribute to the dropout of girls in primary education levels in central Kibosho (Tanzania). It has carried out a qualitative exploratory study which includes semi-structured interviews with 20 participants and focus groups with 12 teachers. The results show that the dropout of girls has various socioeconomic and gender factors such as poverty; lack of moral support; illiteracy of the parents; initiation rituals; early pregnancy; household chores; lack of resources and motivation of teachers in rural schools. Following the results; the paper presents a series of recommendations to both the government of Tanzania and the various educational agents to prevent dropout of girls and young women.